SOCIAL PSYCHOLOGICAL ASPECTS OF PREPARING GIRLS FOR FAMILY LIFE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article talks about female students, their psychological preparation for family life, factors influencing the formation of their perceptions of family life, values and traditions typical of Uzbek families.